TROCHUS SP : PENDEKATAN EKOLOGI DAN BIOLOGI - Achyani, Ratno (Jurnal Harpodon Borneo, 2011)
Trochus sp was gastropod which is a herbivore. Have a natural habitat in coral reefs of the Indo-Pacific waters. In addition to consumption, shell Trochus sp. has the highest economic value which caused the demand is high, and resulting the reduction in natural populations. Trochus sp including one of protected species in Vietnam. Basic information about the ecology and reproductive biology of Trochus sp can provide the knowledge to assure the survival and availability of these organisms in nature. Trochus sp plant-eating animals, and eat green plants and red algae (Cyanophycae and Phaeophycae). They also looking in benthic area for diatoms and benthic foraminifera (Asano 1944). The Natural habitat of Trochus sp in the coral reefs, usually found in the area of reef flat. Maximum density found in reef areas are facing the wind but can also be found on the coral reefs that are at lower limit of the wind, in the intertidal zone and subtidal zone in shallow water (Kitutani and Yamakawa 1999). The maximum depth of Trochus sp to growing was to 10 m, although they can also be found at a depth of 25 m (Bertram 1998). Trochus have spawning at the high tide, with external fertilization and performed at night (nocturnal spawning). According to Sims (1988), Trochus spawn approximately three to five times a year. Small Trochus can growth faster than adults. The higher of Trochus growth rate is in the dry season (March to October) compared to the rainy season (November to March). Keywords : habitat, feed habit, reproduction, life cycle